SIKAP BERBAHASA INDONESIA SISWA KELAS X SMA NEGERI 1 KOTA METRO PROVINSI LAMPUNG - Ratih Rahayu (Balai Bahasa Provinsi Riau, 2014)
Today the use of Indonesian well and properly in sudents' communication declines. The declining spirit of using Indonesian well and properly is currently an important topic to be studied. This study aimed to describe the attitude of using Indonesian language and the factors that causes of students' language attitudes SMA Negeri 1 Metro. The technique of collecting data is by using questionnaire. The data were processed and analyzed by using a qualitative approach. The results showed that students' attitudes in Indonesian language is still quite good. This is evidenced by the answers of all respondents who feel proud to be able to speak Indonesian and 95% of respondents would continue to study the Indonesian although they have already mastered several foreign languages. The dominan factor that causing the attitude of students' language is experience as proved by the responses to questionnaires which mostly have a percentage above 80%.